The Concept of Character Learning: A Comparative Study of Al-Ghazali and Thomas Lickona’s Perspectives - Syamsul Huda; Muhamim Sarifudin; Munifah Munifah; Anis Humaidi; Saifullah Idris; Mawardi Mawardi (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2022)
The main goal in character education is to achieve noble character to create a harmonious human life, helping each other, being fair, and having a balanced relationship in social life. Because of that, instilling character in students is fundamental so that when they grow up, they can become the next generation of solid character. This study uses library research that compares the concept of learning the character of al-Ghazali and Thomas Lickona. The research method carried out in this study was carried out with several steps, such as collecting qualitative data based on reputable data sources and analyzing data to obtain final results. The study results show that Al-Ghazali's educational method is a traditional nuanced method of